2014
DOI: 10.2147/ott.s41828
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of sorafenib in the treatment of Chinese patients with renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) accounts for 3% of all malignancies, and is the most aggressive cancer of the genitourinary system. Metastatic RCC is naturally resistant to chemotherapy and radiotherapy, and immunotherapy is of little benefit. In recent years, the emergence of molecular-targeted therapies has largely changed the therapeutic approach to metastatic RCC. These novel multikinase inhibitors have now become first-choice therapy because of their activity in inhibiting both cell proliferation and tumor ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
35
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 62 publications
6
35
1
Order By: Relevance
“…The discrepancy may be related to diversity of patient populations enrolled in each study differing in many aspects related to prognosis and ethnicity. Furthermore, studies suggest that compared with Western patients, Chinese patients respond better to sorafenib as first-line targeted therapy [36, 37] Also, the results from TIVO-1 trial suggested that sorafenib as a first-line mRCC therapy yielded PFS of 9.1 month [38], which was lesser than the findings from the present study (PFS 11.1 months). Hence, the present study findings further support the previous findings with regards to superior efficacy of sorafenib in Chinese patients with mRCC.…”
Section: Discussioncontrasting
confidence: 75%
“…The discrepancy may be related to diversity of patient populations enrolled in each study differing in many aspects related to prognosis and ethnicity. Furthermore, studies suggest that compared with Western patients, Chinese patients respond better to sorafenib as first-line targeted therapy [36, 37] Also, the results from TIVO-1 trial suggested that sorafenib as a first-line mRCC therapy yielded PFS of 9.1 month [38], which was lesser than the findings from the present study (PFS 11.1 months). Hence, the present study findings further support the previous findings with regards to superior efficacy of sorafenib in Chinese patients with mRCC.…”
Section: Discussioncontrasting
confidence: 75%
“…Sorafenib, as an oral multi-target anti-tumor drug, has achieved remarkable efficacy in the treatment of advanced RCC, effectively prolonging PFS and OS, and has become the recommended first-line treatment for advanced RCC [7,[18][19][20]. Strong evidence exists that sorafenib treatment for advanced results in longer RCC, PFS, and OS in Asian populations than in European and US populations, indicating that sorafenib is particularity advantageous in the treatment of advanced RCC in Asian patients [6,21,22]. Similar to other targeted drugs for tumor treatment, however, patients develop resistance to sorafenib, leading to disease progression and death.…”
Section: Discussionmentioning
confidence: 99%
“…Sorafenib is an oral multi-kinase inhibitor that targets tumor proliferation and angiogenesis and promotes apoptosis by inhibiting multiple intracellular kinases (CRAF, BRAF, and mutant BRAF) and cell surface kinases (KIT, FLT-3, RET, VEGFR-2, VEGFR-3, and PDGFR-B). The efficacy of sorafenib in RCC has been previously confirmed in phase II and phase III trials, leading to its approval by the US Food and Drug Administration in December 2005 as the first targeted agent to show clinical activity against RCC [6]. Previous studies, including the pivotal TARGET trial, have shown promising evidence for sorafenib administered at 400 mg twice daily as both a first-line and second-line therapy for advanced RCC, primarily in Western populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al [6] compared sorafenib outcomes between Chinese and Caucasian RCC patients. Sorafenib appeared to be more effective in patients of Chinese ethnicity than in Caucasian patients.…”
mentioning
confidence: 99%